Relationship of serum CEA levels to tumour size and CEA content in nude mice bearing colonic-tumour xenografts. - Lewis, J. C. (Nature Publishing Group, 1981)
The relationship of serum carcinoembryonic antigen (CEA) levels to tumour size and antigen content was studied in nude mice bearing well differentiated, mucinous human colonic-tumour xenografts. Blood samples were taken from normal nude mice and others bearing xenografts, whose size had been calculated from in vivo measurements; saline and KCl extracts were made of a proportion of these tumours. Sera and tissue extracts were assayed for CEA activity by double-antibody radioimmunoassay. Extracts were also made from the livers and spleens of tumour-bearing and normal nude mice. All normal sera and 78% of sera from tumour-bearing animals had CEA values less than 11.4 ng/ml. No clear correlation was found between serum CEA levels greater than 11.4 ng/ml and tumour size or weight, or between serum CEA and tumour CEA concentrations or total CEA burden. The concentration of CEA in those tumours tested varied from 1 to 22 microgram/g. Our results confirm and extend the conclusions reached by others (Stragand et al., 1980) studying the significance of serum CEA levels with xenograft model systems. The complexity of factors contributing to circulating CEA is discussed in the light of our findings. IMAGES: